Better learning in schools to improve attitudes toward abstinence and intentions for safer sex among adolescents in urban Nepal - Shrestha, Rachana Manandhar (BioMed Central, 2013)
BACKGROUND: School-based sex education is an effective medium to convey health information and skills about preventing sexually transmitted infections (STIs) and unwanted pregnancies among adolescents. However, research on school-based sex education is limited in many developing countries, including Nepal. This study thus had two main objectives: (1) to assess students’ evaluation of school-based sex education, and (2) to examine the associations between students’ evaluations of school-based sex education and their (a) attitudes toward abstinence and (b) intentions for safer sex. METHODS: This cross-sectional study was conducted among 634 students from six schools in the Kathmandu Valley during May–June 2010. We used a self-administered questionnaire to assess students’ evaluations of school-based sex education, attitudes toward abstinence, and intentions for safer sex. The data were then analyzed using multiple linear regression models. RESULTS: Regarding “information on HIV and sexual health”, many students perceived that they received the least amount of information on HIV counseling and testing centers (mean 2.29, SD 1.00) through their schools. In terms of “support and involvement of teachers and parents” in sex education, parents’ participation ranked as the lowest (mean 1.81, SD 1.01). Audiotapes were reported as the least used among the listed “teaching aids for sexual health education” (mean 1.54, SD 0.82). In multivariate analysis, receiving more “information on HIV and sexual health” was positively associated with more positive “attitudes toward abstinence” (β = 0.11, p = <0.018) and greater “intentions for safer sex” (β = 0.17, p = <0.001) among students. Similarly, increased “support and involvement from teachers and parents” was also positively associated with more positive “attitudes toward abstinence” (β = 0.16, p = <0.001) and greater “intentions for safer sex” (β = 0.15, p = <0.002). CONCLUSION: Our results suggest that students’ needs and expectations regarding HIV and sexual health education are not being met through their schools. Moreover, comprehensive information on HIV and sexual health along with increased support and involvement of teachers and parents in sex education might help to improve adolescents’ attitudes toward abstinence and intentions for safer sex. Adapting future school-based interventions to incorporate such elements may thus be an effective strategy to promote adolescent sexual health.